Dynamics and Reversibility of the DNA Methylation Landscape of Grapevine Plants (Vitis vinifera) Stressed by In Vitro Cultivation and Thermotherapy - Baránek, Miroslav; Čechová, Jana; Raddová, Jana; Holleinová, Věra; Ondrušíková, Eva; Pidra, Miroslav (PloS one, 2015)
There is relatively little information concerning long-term alterations in DNA methylation following exposure of plants to environmental stress. As little is known about the ratio of non-heritable changes in DNA methylation and mitotically-inherited methylation changes, dynamics and reversibility of the DNA methylation states were investigated in grapevine plants (Vitis vinifera) stressed by in vitro cultivation. It was observed that significant part of induced epigenetic changes could be repeatedly established by exposure to particular planting and stress conditions. However, once stress conditions were discontinued, many methylation changes gradually reverted and plants returned to epigenetic states similar to those of maternal plants. In fact, in the period of one to three years after in vitro cultivation it was difficult to distinguish the epigenetic states of somaclones and maternal plants. Forty percent of the observed epigenetic changes disappeared within a year subsequent to termination of stress conditions ending and these probably reflect changes caused by transient and reversible stress-responsive acclimation mechanisms. However, sixty percent of DNA methylation diversity remained after 1 year and probably represents mitotically-inherited epimutations. Sequencing of regions remaining variable between maternal and regenerant plants revealed that 29.3% of sequences corresponded to non-coding regions of grapevine genome. Eight sequences (19.5%) corresponded to previously identified genes and the remaining ones (51.2%) were annotated as "hypothetical proteins" based on their similarity to genes described in other species, including genes likely to undergo methylation changes following exposure to stress (V. vinifera gypsy-type retrotransposon Gret1, auxin-responsive transcription factor 6-like, SAM-dependent carboxyl methyltransferase).
Keywords: DNA Methylation; Temperature; Vitis; elektroforéza kapilární; metylace DNA; vysokoúčinná kapalinová chromatografie; Sequence Analysis, DNA; epigeneze genetická; sekvenční analýza DNA; Chromatography, High Pressure Liquid; Stress, Physiological; DNA rostlinná; DNA, Plant; rostlinné buňky; Plant Cells; Electrophoresis, Capillary; teplota; fyziologický stres; Epigenesis, Genetic